Intravenous lipid emulsion for treatment of local anesthetic toxicity - M Caroline Kosh; April D Miller; Jill E Michels (Dove Medical Press, 2010)
M Caroline Kosh, April D Miller, Jill E Michels, , Department of Clinical Pharmacy and Outcomes Sciences, South Carolina College of Pharmacy, University of South Carolina Campus, Columbia, South Carolina, USADate of Preparation: 14th July 2010 Conflict of interest: None declaredClinical question: Is intravenous lipid emulsion a safe and effective therapy for the reversal and treatment of local anesthetic toxicity?Results: Systematic reviews, human case reports, and experimental animal studies have demonstrated the efficacy of intravenous lipid emulsion therapy in successfully reversing cardiac arrhythmias, cardiac arrest, and cardiac collapse seen with severe systemic local anesthetic toxicity. There are fewer data to support treatment of neurologic toxicities associated with local anesthetics.Implementation: Intravenous lipid emulsion 20% should be available whenever patients receive large doses of local anesthetics in operating rooms and emergency departments. Various dosing protocols have been published in the medical literature. Although the dosing protocols are based on low-level evidence, a lack of major adverse events makes lipid emulsion an appropriate therapy for treating cardiotoxic symptoms induced by local anesthetics.Keywords: intravenous lipid emulsion, local anesthetics